Letter: The Formation of Ion Packages with Ultrashort Duration in a Laser Ion Source. Issue 2 (April 2015) - Sysoev, Alexander A.; Karpov, Alexander V.; Gracheva, Oksana I.
A new approach to the formation of ultrashort laser ion packages in the ion source of a time-of-flight (TOF) mass spectrometer for elemental analysis is described. This is achieved by installing a wedge-shaped reflector with special correcting plates. The reflector provides time and space focusing of the ion packages. Such time focusing allows the reduction of the ion package duration up to 1 ns. The proposed approach allows more than an order of magnitude increase in the resolution of the laser TOF mass spectrometer with an axially symmetric electrostatic analyzer to 10, 000–13, 000. In this Letter the theoretical calculations justifying the proposed method are presented.